Attitude toward flexible learning of college students in Albay, Philippines - Bercasio, Rebecca Rosario Oroña; Dugan, Marinel Agustin (International Journal of Evaluation and Research in Education (IJERE), 2025)
Instructional delivery was significantly disrupted by the COVID-19 pandemic worldwide, which led to a flexible modality of teaching-learning. This flexible learning modality challenged the readiness of schools and affected the students. This study determined college students’ attitudes toward flexible learning during the COVID-19 pandemic in Albay Province, Philippines, using the explanatory sequential design of the mixed-methods approach. Data were gathered from 365 college students using an online survey, virtual focus group discussions, and informal interviews with 20 students. Salient findings showed that the students generally had favorable attitudes toward flexible learning, with favorable attitudes toward four dimensions: attitudes toward the teacher, learning resources, teaching methods and learning tasks, and technology tools, and neutral attitudes in two dimensions, namely, attitude toward assessment and support services. The students revealed favorable, neutral, unfavorable, and a combination of attitudes toward flexible learning as discerned from their experiences. The students’ experiences indicate that inspiring and competent teachers are crucial figures in sustaining a favorable attitude of students toward flexible learning. This study provides insights into the gaps in implementing flexible learning through the students’ perspectives, especially regarding the schools’ readiness for and improvement of flexible learning in the post-COVID-19 pandemic.